Financial Performance of Banking Institutions: The Role of Management Ownership, Independent Commissioners, and Audit Committee - Arjang, Arjang; Rahman, Abdul (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This research examines the impact of implementing effective corporate governance practices on the financial performance of banking firms publicly traded on the Indonesia Stock Exchange (IDX). The study focuses on banking businesses listed on the Indonesia Stock Exchange, including the population for analysis. A purposive sampling method was employed to select eight banking companies for the study. The utilized data source comprises secondary data consisting of annual report information about banking institutions. The employed data analysis methodology involves the application of the classical assumption test, which encompasses a normality test, a heteroscedasticity test, and a multicollinearity test. Additionally, all hypotheses are examined by partial, simultaneous, and determination coefficient tests. This study's findings suggest a favorable relationship between managerial ownership and independent commissioners; however, this relationship does not significantly impact financial performance. The audit committee has a notable and substantial impact on the financial performance of banking firms publicly traded on the Indonesia Stock Exchange (IDX).